The heme detoxification pathway : towards the development of a predictive model for the identification and validation of new β hematin inhibitors - Myburgh, Dirkie Coenraad (Stellenbosch : Stellenbosch University, 2023)
Myburgh, Dirkie Coenraad. 2023. The heme detoxification pathway : towards the development of a predictive model for the identification and validation of new β hematin inhibitors. Unpublished doctoral dissertation. Stellenbosch : Stellenbosch University [online]. Available at: https://scholar.sun.ac.za/items/a0e16696-23d6-485b-a6cc-954152467be1